2004
DOI: 10.1097/01.ju.0000130674.86474.7f
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expanding Polytetrafluoroethylene Covered Nitinol Stents for the Treatment of Ureteral Stenosis: Preliminary Report

Abstract: We found that ePTFE covered nitinol stents were safe and effective for ureteral stenosis. Their resistance to calcification was high with nonobstructive hyperplasia developing in only a few cases and only at the stent ends. The ideal material for covering stents would produce no mucous hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Variable patency rates (51.2 to 100%) are reported for various types of metallic ureteral stents used in the treatment of ureteral obstruction irrespective of cause [15,17,22,23]. In our study, the UVENTA stents were not obstructed during follow-up, so that the overall patency rate was 100%.…”
Section: Discussionmentioning
confidence: 55%
“…Variable patency rates (51.2 to 100%) are reported for various types of metallic ureteral stents used in the treatment of ureteral obstruction irrespective of cause [15,17,22,23]. In our study, the UVENTA stents were not obstructed during follow-up, so that the overall patency rate was 100%.…”
Section: Discussionmentioning
confidence: 55%
“…The studies were published over a period of 23 years (1992–2016) and included 21 prospective and 10 retrospective studies. These studies reported the effectiveness of specific MSs in population studies [1] , [2] , [3] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , in comparative studies between different MSs [28] and between MSs and JJ stents [29] , [30] . It should be noted that all comparative studies were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Urinary obstruction in conjunction with the foreign material of the stent and incrustations are also risk factors for recurrent urinary tract infections, resulting in lumbar pain, hematuria, dysuria, and fever. To overcome the drawbacks of a nitinol mesh stent in the urinary tract, polytetrafluoroethylene-covered nitinol stents were developed and had promising short-term results [ 15 ]; however, distal migration of such stents poses a considerable problem [ 16 ].…”
Section: Discussionmentioning
confidence: 99%